Health education affects knowledge in the management of dysmenorrhea in adolescent girls - Ayu Lestari; Rokhanawati, Dewi (Universitas 'Aisyiyah Yogyakarta, 2024)
Dysmenorrhea or menstrual pain is a complaint caused by a hormonal imbalance that results in the onset of pain that is most often experienced by adolescents. The management of dysmenorrhea varies, such as pharmacological and non-pharmacological management. The purpose of this study is to determine the influence of health education on dysmenorrhea management knowledge in adolescent girls at SMP Negeri 2 Godean, Sleman, Yogyakarta. The design of this study is an experimental quasy using a nonequivalent control group design approach. The respondents in this study were 44 class VII students with purposive sampling techniques. This research instrument uses a questionnaire. The analysis methods used were univariate and bivariate analysis (paired sample t-test and independent sample t-test). The results showed that in the intervention group, the average score before being given health education was 61.45 and the average value after being given health education was 89.91, while in the control group there was no increase. The results of the paired sample t-test obtained a p-value = 0.000 (<0.05) meaning that there is an influence of health education on dysmenorrhea management knowledge. The results of the independent sample t-test obtained p value = 0.000 (<0.05) meaning that there was a significant difference between the level of knowledge of female students in the intervention group and the control group. The conclusion that there is an influence of health education on the knowledge of dysmenorrhea management in adolescent girls at SMP Negeri 2 Godean, Sleman, Yogyakarta.